2013
DOI: 10.1111/j.1476-5381.2012.01857.x
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting cardiovascular regeneration with bone marrow‐derived angiogenic and vasculogenic cells

Abstract: Cell-based therapy has emerged as a promising therapy for cardiovascular disease. Particularly, bone marrow (BM)-derived cells have been most extensively investigated and have shown encouraging results in preclinical studies. Clinical trials, however, have demonstrated split results in post-myocardial infarction cardiac repair. Mechanistically, transdifferentiation of BM-derived cells into cardiovascular tissue demonstrated by earlier studies is now known to play a minor role in functional recovery, and humora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 174 publications
(197 reference statements)
0
12
0
Order By: Relevance
“…Under some pathological conditions, such as in diabetic patients, the functional activity and even the structure of endothelial cells are damaged, which may contribute to micro-and macro-vascular abnormalities (Paneni et al, 2013;Lee et al, 2013). EPCs, a group of multi-progenitor cells, having the ability to differentiate into endothelial cells and contributing to endothelial recovery (Asahara et al, 1997;Lee and Yoon, 2013) plays a critical role in vascular endothelium integrity, in vascular repair and regeneration (Inoue et al, 2011;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under some pathological conditions, such as in diabetic patients, the functional activity and even the structure of endothelial cells are damaged, which may contribute to micro-and macro-vascular abnormalities (Paneni et al, 2013;Lee et al, 2013). EPCs, a group of multi-progenitor cells, having the ability to differentiate into endothelial cells and contributing to endothelial recovery (Asahara et al, 1997;Lee and Yoon, 2013) plays a critical role in vascular endothelium integrity, in vascular repair and regeneration (Inoue et al, 2011;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that EPCs plays a critical role in vascular endothelium integrity, in vascular repair and regeneration (Inoue et al, 2011, Liu et al, 2011. Accumulating evidences suggest that circulating EPCs, derived from the bone marrow, contribute to endothelial recovery (Lee and Yoon, 2013). Decreased levels of circulating EPCs are correlated with increased risk for coronary artery disease (Briguori et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The collective data to date has shown that the dominant mechanisms underlying vascular regenerative effects of adult stem or progenitor cells are their paracrine activities (reviewed in [57]). Based on this, we sought to identify higher angiogenic cells regardless of their stem cell status and discovered that a subpopulation of BM or peripheral blood MNCs expressing CD31 have these high angiogenic activities and are effective for vascular repair [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…While the embryonic stem cell remains the most obvious candidate to produce the billions of cells needed for significant myocardial repair, considerable ethical and practical considerations still need to be overcome. Advances in the field of research associated with regenerative medicine have resulted in the identification of therapeutic regenerative potential in existing cell types (see accompanying review by Lee and Yoon, 2012). This could provide new pharmaco- Table 3 Paracrine factors/cytokines secreted by stem/progenitor cells and implicated in myocardial repair…”
Section: Figurementioning
confidence: 99%